Religiusitas dan Strategi Coping Stres Santri Remaja - Fauzul Adim Ubaidillah; Moh. Rizki Jaelani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Stress is something that inevitably occurs in every individual, including in the minds of every Islamic boarding school student. The busy schedule and academic demands make students prone to feeling depressed and vulnerable to stress. This requires good stress coping strategies to overcome every problem that arises. One factor that can increase the ability to deal with stress is religiosity. This study aims to determine whether there is a relationship between religiosity and stress coping strategies among students. The participants of this study were 130 students selected using purposive sampling. The research instruments used were a religiosity scale and a stress coping strategy scale. The results showed that stress coping strategies have a positive and significant relationship with religiosity. An R Square value of 0.329 indicates that religiosity contributes 32.9 percent to the students' coping strategy abilities.